Blessed events : religion and home birth in America - Klassen, Pamela E. (Pamela Edith), 1967- (Princeton studies in cultural sociology., 2001)
"Blessed Events explores how women who give birth at home use religion to make sense of their births and in turn draw on their birthing experiences to bring meaning to their lives and families."--Back cover